Threat or opportunity: accelerated job demands during COVID-19 pandemic - Leila Afshari; Aamir Hayat; K.K. Ramachandran; Bartram, Timothy; Bamini KPD Balakrishnan (Emerald Publishing Limited, 2022)
Purpose: The purpose of this study is to investigate the effects of accelerated job demands on employee outcomes during the COVID-19 crisis. An integrated model was developed to explore the relationships between different types of job demands (learning, decision-making, work intensification), employee turnover intention (TI) and burnout (BU). Design/methodology/approach: Data were obtained from professionals whose work conditions were impacted by the COVID-19 pandemic crisis. An online survey was distributed anonymously. A total of 566 questionnaires were included in the analysis. Structural equation modeling was employed to analyze the data. Findings: The findings revealed that employees' perception of job demands impacts the significance and direction of the relationships between different forms of job demands and employee outcomes. Furthermore, the findings confirm that mediating role of perceived organizational support alleviates the adverse effects of job demands on employee outcomes. Finally, the present study supported the moderation effect of positive affectivity between work intensification and employee BU. Practical implications: This study provides employers with insights about supporting employees to cope with increased job demands in conditions where rapid changes are inevitable. Originality/value: The unique context of research (COVID-19) enabled this study to account for the acceleration of job demands that employees experience in rapidly changing situations. This study employed an instrument that allowed for the assessment of acceleration in job demands. Furthermore, the granular approach of the measurement model extended the perspectives of job demands and work intensification.